31.F. Workshop: Health system (performance) assessment: working towards a common approach. (30th September 2020) - ,; ,
Abstract: Since the publication of the World Health Report 2000, which aimed at assessing health systems performance globally, a number of health systems performance assessment (HSPA) frameworks and tools, designed for various purposes, have emerged. In 2017, the joint Universal Health Coverage 2030 Technical Working Group on Health Systems Assessment (TWG), consisting of health policy makers and global actors, such as the WHO, World Bank, USAID, Unicef, European Commission, OECD, etc., was formed with the aim to align the existing tools and develop a common approach to understanding and measuring health systems performance globally. As part of this work, the European Observatory on Health Systems and Policies (OBS) has developed a Health Systems Performance Assessment framework for Universal Health Coverage (HSPA Framework for UHC), that allows to evaluate health system performance, largely by drawing on the information available in the existing tools or through global data collection initiatives. Suggested approach is based on the detailed assessment of the four health system functions (governance, financing, resource generation and service delivery) and their sub-functions, the interaction of which jointly leads to the successes and failures in the achievement of health system goals. We propose distinct assessment areas for specific functions and sub-functions as a way to identify potential strengths and weaknesses, which can then be related to actions or responsibilities of specific actors within a health system, or linkages to other sectors. The objective of the workshop is to introduce the background, rationale, methods and process of developing of the HSPA framework for UHC; present a systematic approach to assessing various functions of health system and their interactions; relate the assessment areas of specific functions and sub-functions to the final health system goals; and, finally, to test the use of the framework in practice. The workshop is structured as follows: the workshop will start from the four 10-minute presentations (outlined below), followed by an interactive session with the audience to discuss the content of the framework and elaborate on its potential use for HSPA and applications globally. Key messages: The HSPA framework for UHC is an approach that allows to bring together existing HSPA efforts and moves towards a more systematic and universally applicable health system performance assessment. The approach assesses performance through attribution of various health system outcomes to specific functions and sub-functions, allowing to identify strengths and weaknesses that affect performance.